The most effective leadership style in pursuit of resilient supply chain: Sequential mediation of flexibility and agile supply chain - Muhammad Imran Taseer; Alia Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
This study investigates the most effective leadership style of supply chain (SC) management leaders in pursuit of resilient supply chain through the comparison of transformational and transactional leadership styles. Flexibility and agile supply chain are considered as a mechanism which can strengthen the impact of leadership styles on resilient supply chain. However, these phenomena are not addressed in prior studies. We also empirically teste cost-effective mechanism to SMEs for improving supply chain resilience. The constructs are adopted from existing literature to formulate four hypotheses to meet the study objectives. Primary data is collected by incorporating split survey method and time-lagged of two weeks from 317 supply chain professionals working in SMEs manufacturing enterprises of Pakistan via a pre-tested survey instrument. The PROCESS Macros is used to test the hypothesized model. The results reveal the positive significance of both leadership styles with resilient supply chain directly as well as the mechanism of flexibility and agile supply chain. However, the empirical investigation finds that the supply chain managers with transactional leadership style are more effective in pursuit of resilient supply chain directly and through the sequential mediation of flexibility and agile supply chain as compared with other leadership style. The results of this study empirically prove the significance of transformational and transactional leadership with resilient supply chain. The sequential mediation of flexibility and agile SC between leadership styles and resilient supply chain is also proved. The study tests the most effective leadership style which can more strongly influence the resilient supply chain through the comparison of transformational and transactional leadership styles. All of these relationships have not been previously tested. Thus, the study provides an important contribution to existing body of knowledge.
Keywords: 330; resilient supply chain; agile supply chain; flexibility; transformational leadership; transactional leadership; SMEs; manufacturing enterprises; Pakistan